2022
DOI: 10.3389/fmolb.2022.843234
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prognostic Biomarkers in Patients With Malignant Rhabdoid Tumor of the Kidney Based on mTORC1 Signaling Pathway-Related Genes

Abstract: Background: Malignant rhabdoid tumor of the kidney (MRTK) is an infrequent malignant tumor in childhood, accounting for approximately 2% of all childhood kidney tumors. Although the development of current treatments, the overall survival (OS) rate of MRTK patients is only 25%. The aim of this research was to explore the prognostic value of genes associated with the mTORC1 signaling pathway in MRTK.Methods: The transcriptome data of MRTK samples were downloaded from the TARGET database. The 200 genes of HALLMAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…In addition, our previous study found that PI3K-AKT-mTORC1 signaling pathway may play a key role in the development of MRTK [33]. Moreover, we found that P4HA1, AURKA, GOT1 and MLLT11 are expected to become new targets for the diagnosis and treatment of MRTK [34]. However, the efficacy and safety of treatment still need to be confirmed by international cooperation and large sample prospective studies.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, our previous study found that PI3K-AKT-mTORC1 signaling pathway may play a key role in the development of MRTK [33]. Moreover, we found that P4HA1, AURKA, GOT1 and MLLT11 are expected to become new targets for the diagnosis and treatment of MRTK [34]. However, the efficacy and safety of treatment still need to be confirmed by international cooperation and large sample prospective studies.…”
Section: Discussionmentioning
confidence: 89%